Evaluation of Elite Spring Wheat Lines for Agro-Morphological Traits and Grain Yield under Late-Sown Condition - Khanal, Dinesh (Genetics, Plant Breeding and Seed Science, 2025)
Testing of wheat genotypes for the late sown condition is limited and little knowledge is available, so this research was carried out to provide insights on the performance of different genotypes in late sown condition. A total of 49 different wheat genotypes acquired from the 15th High-Temperature Wheat Yield Trial and local check Gautam were studied for agro-morphological characters, yield, and yield attributing traits at the farmer’s field in Jamuniya, Nawalparasi, Nepal. The research was carried out from December 2016 to April 2017 in the alpha lattice design with two replications. Analysis of variance revealed that days to booting, days to heading, and thousand-grain weight were significantly different. Similarly, the studied genotypes showed significant differences in the number of effective tillers and harvest index. Non-significant differences between the genotypes were observed for emergence count, physiological maturity, plant height, spike length, number of grains per spike, biological yield, and grain yield. Based on correlation analysis of selected traits, all traits showed significant correlations with grain yield. Biological yield (0.950**), plant height (0.901**), and spike length (0.716**) were positively and highly correlated with grain yield. Similarly, the number of tillers (0.548**), thousand-grain weight (0.510**), and number of grains per spike (0.509**) had a positive correlation with grain yield. The study has indicated that biological yield, plant height, spike length, and the number of effective tillers per square meter could be valuable traits for the higher yield in late-sown conditions.